MinION Whole‑Genome Sequencing in Resource‑Limited Settings: Challenges and Opportunities - Wasswa, Fredrickson B.; Kassaza, Kennedy; Nielsen, Kirsten; Bazira, Joel (Current Clinical Microbiology Reports, 2022)
The introduction of MinION whole-genome sequencing technology greatly increased and simplified complete genome sequencing in various fields of science across the globe. Sequences have been generated from complex organisms to microorganisms and are stored in genome databases that are readily accessible by researchers. Various new software for genome analysis, along with upgrades to older software packages, are being generated. New protocols are also being validated that enable WGS technology to be rapidly and increasingly used for sequencing in field settings. MinION WGS technology has been implemented in developed countries due to its advantages: portability, real-time analysis, and lower cost compared to other sequencing technologies. While these same advantages are critical in developing countries, MinION WGS technology is still under-utilized in resource-limited settings. In this review, we look at the applications, advantages, challenges, and opportunities of using MinION WGS in resource-limited settings.